Opportunities and Challenges of Religious Character Education for Madrasah Ibtidayyah Students in The Era of Society 5.0 - Ramadhani, Khalilah; Febriani, Suci Ramadhanti (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2022)
Entering the era of society 5.0 has brought changes. This is great for educational institutions that rely on digital technology as a means of achieving national education goals. However, despite the many benefits of technology in the world of education, the character of students is slowly starting to be eroded due to unfriendly access to information. This creates various challenges and opportunities for teachers to provide religious character education to students through digital technology in the era of society 5.0. This study uses a qualitative library research method. Literature data was collected through various sources of books, scientific articles and using content analysis techniques. The results of the study show that the challenges of religious character education in the era of society 5.0 consist of minimal parental knowledge about character education, no parental control, limited and unequal resources, technological innovation that causes a loss of control, and no interaction and socialization. Meanwhile, opportunities for religious character education in the era of society 5.0 consist of supporting technology, teacher competence, varied strategies, and building competence, innovation and student achievement. This study recommends further research to explore character education through more diverse methods and wider research objects.